Project-oriented leadership - Müller, Ralf, 1957- (Advances in project management., 2010)
Projects need leaders who can give them vision, identity, keep the stakeholders and the project team on board and make the difficult decisions. This book explains the key leadership models and shows how they can be applied within projects to lead processes, functions and people and ensure an ethical and inclusive approach within projects and programs.